Revisiting the Customs Act 1969 in line with WCO’s International Convention on the Simplification and Harmonization of Customs Procedures 1974 - Islam, Mohammad Towhidul; Alam, Khurshid (Faculty of Law, University of Jember, Indonesia, 2023)
In the present-day system of integrated world economy, the administration of customs or customs procedure clearly carries considerable effects on the trade transactions both within the border and beyond. In fact, the gravity of the cross-border business potentials leads to the realization of simplifying and harmonizing the customs procedures all over the world. Moreover, the development and operation of the modern customs administration signifies, by and large, a radical shift from the revenue collection to the trade facilitation focus. In the current day, it has become almost a universal belief that trade facilitation and removal of trade barriers go hand in hand with simplification and harmonization of customs procedures. The World Customs Organization (WCO) with this in mind had the Revised Kyoto Convention (RKC) enacted in 1974. The customs regime of Bangladesh is still dependant on the half century old the Customs Act, 1969. Although some changes have been brought to bring it in line with the RKC, many of its provisions are still the same. This creates an impediment towards trade facilitation and economic growth. This paper discusses the differences between the provisions of RKC and Customs Act, 1969 and recommends the changes that are required to be brought in the customs regime of Bangladesh for overall trade facilitation and economic development of the country.